Inhibition of cotranslational translocation by apratoxin S4: Effects on oncogenic receptor tyrosine kinases and the fate of transmembrane proteins produced in the cytoplasm - Weijing Cai; Ranjala Ratnayake; Mengxiong Wang; Qi-Yin Chen; Kevin P. Raisch; Long H. Dang; Brian K. Law; Hendrik Luesch (Elsevier, 2021)
Receptor tyrosine kinases (RTKs) have become major targets for anticancer therapy. However, resistance and signaling pathway redundancy has been problematic. The marine-derived apratoxins act complementary to direct kinase inhibitors by downregulating the levels of multiple of these receptors and additionally prevent the secretion of growth factors that act on these receptors by targeting Sec61α, therefore interfering with cotranslational translocation. We have profiled the synthetic, natural product-inspired apratoxin S4 against panels of cancer cells characterized by differential sensitivity to RTK inhibitors due to receptor mutations, oncogenic KRAS mutations, or activation of compensatory pathways. Apratoxin S4 was active at low-nanomolar to sub-nanomolar concentrations against panels of lung, head and neck, bladder, and pancreatic cancer cells, concomitant with the downregulation of levels of several RTKs, including EGFR, MET and others. However, the requisite concentration to inhibit certain receptors varied, suggesting some differential substrate selectivity in cellular settings. This selectivity was most pronounced in breast cancer cells, where apratoxin S4 selectively targeted HER3 over HER2 and showed greater activity against ER+ and triple negative breast cancer cells than HER2+ cancer cells. Depending on the breast cancer subtype, apratoxin S4 differentially downregulated transmembrane protein CDCP1, which is linked to metastasis and invasion in breast cancer and modulates EGFR activity. We followed the fate of CDCP1 through proteomics and found that nonglycosylated CDCP1 associates with chaperone HSP70 and HUWE1 that functions as an E3 ubiquitin ligase and presumably targets CDCP1, as well as potentially other substrates inhibited by apratoxins, for proteasomal degradation. By preventing cotranslational translocation of VEGF and other proangiogenic factors as well as VEGFR2 and other receptors, apratoxins also possess antiangiogenic activity, which was validated in endothelial cells where downregulation of VEGFR2 was observed, extending the therapeutic scope to angiogenic diseases.